Alpha-al2o3 platelet three-dimensional interlocking network structure ceramic aerogel and preparation method thereof

CN122916633APending Publication Date: 2026-10-16SHENYANG AEROSPACE UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611078595.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-20
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而,在超过1000℃的极端高温环境中,现有氧化铝气凝胶的服役表现远非理想,主要面临两大瓶颈:一是高温结构失稳

Benefits of technology

1.网络形成机制创新:区别于现有技术依赖外加粘结剂将预制片晶粘接成网络,本发明通过调控冰晶石-碳化硅复合助剂的气相传质效率,在极低固含量的气凝胶骨架中实现了片晶的原位生长和互锁连接,从而首次将互锁结构引入气凝胶领域。在烧结过程中驱动片晶原位生长并自发互锁连接,实现了无外加粘结剂的三维网络构建,避免了粘结剂分布不均、高温界面强度不足等问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916633A_ABST
    Figure CN122916633A_ABST
Patent Text Reader

Abstract

The application discloses an alpha-Al2O3 flake crystal three-dimensional interlocking network structure ceramic aerogel and a preparation method thereof, and belongs to the technical field of new material preparation. The alpha-Al2O3 flake crystal three-dimensional interlocking network structure ceramic aerogel prepared by the application is formed by mutual lap and interlocking of alpha-Al2O3 flake crystals to form a three-dimensional continuous network framework. Based on a cryolite-silicon carbide synergistic mechanism, an external binder is abandoned, and a synergistic gas phase mass transfer effect of a cryolite-silicon carbide composite additive is utilized to drive in-situ growth of alpha-Al2O3 flake crystals and spontaneous interlocking connection in a normal-pressure sintering process, so that the binder interface problem is fundamentally solved, normal-pressure drying is realized, and the ceramic aerogel with high porosity and high strength is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of new material preparation technology, specifically relating to an α-Al2O3 lamellar three-dimensional interlocking network structure ceramic aerogel and its preparation method. Background Technology

[0002] Alumina aerogels, due to their superior properties such as high melting point, low thermal conductivity, and high specific surface area, have broad application prospects in aerospace thermal protection and high-temperature insulation. However, in extreme high-temperature environments exceeding 1000℃, the service performance of existing alumina aerogels is far from ideal, mainly facing two major bottlenecks: First, high-temperature structural instability. When the temperature exceeds 1000℃, traditional amorphous or γ-phase alumina aerogels undergo a structural transformation to the α-phase (γ→α phase transition), leading to rapid shrinkage and collapse of the skeleton, resulting in a precipitous drop in thermal insulation performance. Simultaneously, traditional alumina aerogels are typically composed of a three-dimensional network of nanoparticles, with the particles connected only by sintered necks at point contacts, resulting in inherent defects such as high brittleness and poor mechanical properties. Under long-term high-temperature and complex thermo-mechanical coupling environments, they are highly susceptible to structural failure. Second, high-temperature thermal insulation performance degradation. At high temperatures, radiative heat transfer gradually becomes dominant, and conventional alumina aerogels exhibit significant "transparency" in the critical infrared band, failing to effectively block radiative heat. This causes their high-temperature thermal conductivity to rise rapidly, severely reducing their thermal insulation effect.

[0003] To overcome these challenges, researchers attempted to improve performance by replacing zero-dimensional nanoparticles with one-dimensional / two-dimensional structural units. The team led by Wang Xiaodong and Shen Jun at Tongji University used a polymer microtemplate method to transform the necklace-like structure assembled from nanoparticles into a nanoribbon structure, preparing Al2O3 nanoribbon aerogels. These aerogels could withstand 80% compression without breaking and maintained a 228 μm diameter after heat treatment at 1300℃ for 2 hours. 2 / g specific surface area. Chen Wei et al. prepared alumina nanorod aerogels using boehmite nanorods as raw materials. The aerogels were heat-resistant up to 1400℃ and had a thermal conductivity of 0.0168~0.0254 W·m. -1 ·K -1 The above studies demonstrate that replacing nanoparticles with one-dimensional / two-dimensional structural units is an effective way to improve the performance of alumina aerogels.

[0004] In previous studies of this invention, it was discovered that the synergistic effect of cryolite and silicon carbide can drive the growth of α-Al₂O₃ lamellar crystals and form an interlocking network, successfully preparing porous alumina ceramics with a long-range interlocking lamellar structure (Ceram. Int. 2024, 50, 5585). This technology utilizes NaAl 11 O 17The gas-phase mass transfer effect of NaAlSiO4 promotes the formation of sintering necks between lamellar grains during atmospheric pressure sintering, achieving high strength (60.5 MPa) and high porosity (53.4%) in porous ceramics. However, this technique produces porous ceramic bulk with a relatively high density (approximately 2.1 g / cm³). 3 This makes it difficult to meet the urgent needs of aerospace and other fields for lightweight thermal insulation materials.

[0005] Ji et al. (ACS Appl. Mater. Interfaces 2023, 15, 6848) reported that α-Al2O3 nanosheet aerogels are prepared by using α-Al2O3 nanosheets as assembly units and adding silica sol as a high-temperature binder, followed by freeze-drying and high-temperature sintering. The core idea of ​​this technology is the assembly of pre-formed crystal sheets and binder. Its inherent defects are: (1) it relies on external binders to form a network, resulting in uneven binder distribution and interface weakening at high temperatures; (2) it uses supercritical drying and freeze-drying, which are complex, time-consuming, and costly; (3) the network connection strength is provided only by the binder, and the compressive strength is only 0.6 MPa.

[0006] Academician Yu Shuhong's team used alumina microcrystals as building blocks to prepare nacre-like ceramics through evaporation-induced self-assembly and pressureless sintering, demonstrating that the microcrystals can form interlocking structures during high-temperature sintering. However, this technique produces dense bulk ceramics rather than aerogels, which have low porosity, high density, and insufficient thermal insulation performance. Summary of the Invention

[0007] Therefore, the purpose of this invention is to provide a ceramic aerogel with an α-Al2O3 lamellar three-dimensional interlocking network structure and its preparation method. Based on the previously discovered cryolite-silicon carbide synergistic mechanism, it is extended to the field of aerogels, opening up a completely new technical path: abandoning the addition of external binders, utilizing the synergistic gas-phase mass transfer effect of cryolite-silicon carbide composite additives, the in-situ growth of α-Al2O3 lamellar crystals is driven and spontaneously interlocked during atmospheric pressure sintering, fundamentally solving the binder interface problem, while realizing atmospheric pressure drying, and obtaining a ceramic aerogel with both high porosity and high strength.

[0008] To achieve the above objectives, the present invention provides the following technical solution: In a first aspect, the present invention provides a ceramic aerogel with an α-Al2O3 lamellar three-dimensional interlocking network structure. The α-Al2O3 lamellar three-dimensional interlocking network structure ceramic aerogel is formed by overlapping and interlocking α-Al2O3 lamellars to form a three-dimensional continuous network skeleton. The radial dimension of the α-Al2O3 lamellars is 2~36 μm and the thickness is 0.1~2.5 μm. The aspect ratio of the α-Al2O3 lamellars is 6~46.

[0009] Based on the above technical solution, furthermore, the α-Al2O3 lamellar crystals are connected by a sintering neck and interlocking through a contact interface, without any external binder.

[0010] Based on the above technical solution, furthermore, the porosity of the α-Al₂O₃ lamellar three-dimensional interlocking network structure ceramic aerogel is 50%~95%; the thermal conductivity of the α-Al₂O₃ lamellar three-dimensional interlocking network structure ceramic aerogel at 25℃ is ≤0.08 W·m. -1 ·K -1 Compressive strength ≥ 0.5 MPa.

[0011] Secondly, the present invention provides a method for preparing the α-Al2O3 lamellar three-dimensional interlocking network structure ceramic aerogel, comprising the following steps: (1) Raw material mixing: The organic aluminum precursor and α-Al2O3 powder are mixed at a mass ratio of 1:0.1~1, and a composite sintering aid is added. After ball milling and mixing evenly, a molding slurry is prepared. (2) Molding: The molding slurry is prepared into a blank by gel injection molding process or template foaming method; (3) Drying: The green body prepared in step (2) is dried to obtain the aerogel precursor; (4) Sintering: The aerogel precursor is placed in an air atmosphere and heated to 1100~1300℃ at a heating rate of 1~10℃ / min. It is held for 1~4 hours. The cryolite-silicon carbide synergistic gas phase mass transfer effect drives the in-situ growth of α-Al2O3 lamellar crystals and forms a three-dimensional interlocking network. After sintering, ceramic aerogel is obtained.

[0012] During sintering, cryolite (Na3AlF6) decomposes at high temperatures to generate gaseous species such as AlF3 and NaF, which react with alumina to form an Al-OF gaseous intermediate. This intermediate readily adheres to the (0001) crystal plane of alumina, reducing its surface energy and causing the (0001) crystal plane to expand faster than the (1010) crystal plane, thereby driving anisotropic lamellar growth. Silicon carbide (SiC) oxidizes at high temperatures (e.g., SiC + 2O2 → SiO2 + CO2), consuming local oxygen partial pressure and enhancing gas-phase mass transfer efficiency. Both synergistically promote the formation of sintering necks and mechanical interlocking between lamellar grains, connecting discrete lamellar grains into a three-dimensional interlocking network.

[0013] Based on the above technical solution, the organoaluminum precursor in step (1) is further selected from aluminum sec-butoxide, aluminum isopropoxide, or aluminum acetylacetone.

[0014] Based on the above technical solution, further, the particle size of the α-Al2O3 powder in step (1) is 0.1~10 μm.

[0015] Based on the above technical solution, further, the mass ratio of cryolite to silicon carbide in the composite sintering aid in step (1) is 20~1:1.

[0016] Based on the above technical solution, further, the amount of composite sintering aid added in step (1) is 1% to 20% of the total mass of the organoaluminum precursor and α-Al2O3 powder.

[0017] Based on the above technical solution, further, the gel injection molding process in step (2) is as follows: weigh the monomer and crosslinking agent, add them to deionized water to dissolve them, and prepare a premixed solution; add the ball-milled slurry to the premixed solution, adjust the pH value to 9~10, add 1~2 g of polyacrylic acid (50%, MW~3000) dispersant, stir evenly and then degas under vacuum; add ammonium persulfate (APS) as an initiator, and after injection molding, solidify in a 50℃ water bath, and obtain the green blank after demolding.

[0018] Based on the above technical solution, further, the drying in step (3) is atmospheric pressure drying, freeze drying or supercritical drying.

[0019] Compared with the prior art, the present invention has the following beneficial effects: 1. Innovative Network Formation Mechanism: Unlike existing technologies that rely on external binders to bond pre-formed lamellar crystals into a network, this invention achieves in-situ growth and interlocking connections of lamellar crystals within an aerogel framework with extremely low solid content by controlling the gas-phase mass transfer efficiency of the cryolite-silicon carbide composite additive. This marks the first time that an interlocking structure has been introduced into the aerogel field. During sintering, the in-situ growth and spontaneous interlocking of lamellar crystals are driven, enabling the construction of a three-dimensional network without external binders, thus avoiding problems such as uneven binder distribution and insufficient high-temperature interface strength.

[0020] 2. Structural Morphology Innovation: Compared with previous research (Ceram. Int. 2024, 50, 5585), this invention expands the product morphology from porous ceramics to aerogels. While maintaining the advantages of the interlocking structure, it increases the porosity from 53.4% ​​to over 85% and significantly reduces the density. Compared with the technology of Ji et al., the lamellar crystals in this invention are connected through a dual mechanism of mechanical interlocking and sintering necks, rather than relying on external binders, which significantly enhances the connection strength of the framework. Comparative verification shows that neither cryolite nor silicon carbide alone can form an interlocking structure, proving that the synergistic effect of the two is the key to forming a three-dimensional interlocking network.

[0021] 3. Innovative preparation process: By utilizing the synergistic gas-phase mass transfer effect of cryolite-silicon carbide composite additives, in-situ growth and interlocking connection of lamellar crystals can be achieved during atmospheric pressure sintering. No supercritical drying or complex chemical vapor deposition equipment is required. The process is simple, the production cycle is short, the cost is controllable, and it is easy to scale up production.

[0022] 4. Synergistic Performance Optimization: This invention achieves excellent mechanical properties while maintaining high porosity (50%~95%). Experiments demonstrate that by adjusting the raw material ratio and sintering process parameters, the lamellar size and porosity can be adjusted within a wide range to obtain ceramic aerogels with different mechanical and thermal insulation properties. Comparative examples verify this. Without the addition of cryolite and silicon carbide additives (Comparative Example 1), lamellar networks could not be formed; with only cryolite added but no silicon carbide added (Comparative Example 2), the lamellar networks were not fully developed, and the compressive strength was <0.25 MPa; with only silicon carbide added but no cryolite added (Comparative Example 3), lamellars could not be formed.

[0023] The above comparative examples demonstrate that the synergistic effect of cryolite and silicon carbide is the key to forming a three-dimensional interlocking network of lamellar crystals, a technological concept that has not been reported in the prior art.

[0024] 5. Excellent high-temperature stability: The main crystalline phase of the ceramic aerogel prepared by this invention is α-Al2O3. α-Al2O3 is a thermodynamically stable phase that does not undergo phase change at high temperatures and can be used stably for a long time at temperatures above 1600℃. It is suitable for extreme environments such as aerospace thermal protection and high-temperature insulation. Attached Figure Description

[0025] To more clearly illustrate the embodiments of the present invention, the accompanying drawings involved in the embodiments will be briefly described below.

[0026] Figure 1 The image is a scanning electron microscope (SEM) image of the α-Al2O3 lamellar three-dimensional interlocked network structure ceramic aerogel prepared in Example 1 of this invention.

[0027] Figure 2 The image shows the X-ray diffraction (XRD) pattern of the α-Al2O3 lamellar three-dimensional interlocked network structure ceramic aerogel prepared in Example 1 of this invention. The vertical axis represents the diffraction intensity, the horizontal axis represents the diffraction angle 2θ, and the characteristic peaks mainly correspond to the α-Al2O3 phase. Detailed Implementation

[0028] The present invention will be described in detail below with reference to the embodiments. However, the implementation of the present invention is not limited thereto. Obviously, the embodiments described below are only some embodiments of the present invention. For those skilled in the art, other similar embodiments can be obtained without creative effort and all fall within the protection scope of the present invention.

[0029] Example 1 This embodiment provides a method for preparing α-Al2O3 lamellar three-dimensional interlocking network structure ceramic aerogel, the specific steps of which are as follows: (1) Raw material mixing: Take aluminum sec-butoxide (Aluminum sec-butoxide, C 12 H 27 10 g of AlO3 and 10 g of α-Al2O3 powder (average particle size 3 μm) were mixed evenly. 1 g of cryolite and 1 g of silicon carbide were added, and the mixture was ball-milled for 2 hours (400 r / min) to prepare the molding slurry.

[0030] (2) Molding: Gel injection molding process was adopted. 0.26 g of acrylamide (AM) as monomer and 3.9 g of N,N'-methylenebisacrylamide (MBAM) as crosslinking agent were weighed and dissolved in deionized water to prepare a premix. The ball-milled slurry was added to the premix, the pH was adjusted to 9-10, 1.5 g of polyacrylic acid (50%, MW~3000) dispersant was added, and the mixture was stirred evenly and then degassed under vacuum. Ammonium persulfate (APS) was added as an initiator, and the mixture was cured in a 50℃ water bath after injection molding. After demolding, the green body was obtained.

[0031] (3) Drying: Dry the green body at 80°C and normal pressure for 24 hours to obtain the aerogel precursor.

[0032] (4) Sintering: The aerogel precursor obtained in step (3) is placed in a muffle furnace and heated to 1200°C at 5°C / min under an air atmosphere. It is held for 2 hours and then naturally cooled to room temperature to obtain ceramic aerogel.

[0033] Characterization of the obtained ceramic aerogel: SEM images ( Figure 1 The XRD pattern shows that the radial dimensions of the lamellar crystals are 6-15 μm, and the thickness is 0.2-0.5 μm. The lamellar crystals are interlocked through sintered necks to form a three-dimensional network; XRD pattern ( Figure 2 It exhibits a pure α-Al₂O₃ phase; its porosity is 68%, its compressive strength is 1.2 MPa, and its thermal conductivity is 0.08 W·m. -1 ·K -1 .

[0034] Example 2 The only difference between this embodiment and Example 1 is that the mass ratio of the organoaluminum precursor to α-Al₂O₃ powder is 3:1 (i.e., 15 g of sec-butylaluminum and 5 g of α-Al₂O₃ powder), cryolite is 1.5 g, and silicon carbide is 0.75 g; all other conditions are the same. The resulting ceramic aerogel has a porosity of 85%, a compressive strength of 0.6 MPa, and a thermal conductivity of 0.045 W·m. -1 ·K -1 The lamellar radial dimensions are 2-8 μm, and the thickness is 0.1-0.3 μm.

[0035] Example 3 In this embodiment, aluminum isopropoxide was used instead of sec-butylaluminum in Example 1. The amount of aluminum isopropoxide used was 10 g, and the other conditions were the same as in Example 1. A lamellar three-dimensional interlocking network ceramic aerogel with a similar structure was obtained, with a porosity of 70%, a compressive strength of 1.0 MPa, and a thermal conductivity of 0.06 W·m. -1 ·K -1 .

[0036] Example 4 In this embodiment, the sintering temperature in step (4) was adjusted to 1100℃ and 1300℃, while the other conditions remained the same as in Example 1. This yielded a lamellar three-dimensional interlocking network ceramic aerogel with a similar structure. At a sintering temperature of 1100℃, its porosity was 72%, its compressive strength was 0.9 MPa, and its thermal conductivity was 0.065 W·m. -1 ·K -1 At a sintering temperature of 1300℃, its porosity is 62%, its compressive strength is 1.6 MPa, and its thermal conductivity is 0.078 W·m. -1 ·K -1 .

[0037] Comparative Example 1 The only difference between this comparative example and Example 1 is that cryolite and silicon carbide were not added, while other conditions remained the same. The resulting sample did not form a distinct lamellar network; the lamellar size was small (<2 μm) and dispersed, and no interlocking structure was formed. The compressive strength was 0.4 MPa.

[0038] Comparative Example 2 The only difference between this comparative example and Example 1 is that only cryolite (1 g) was added, without silicon carbide, while all other conditions remained the same. The resulting sample had incomplete lamellar development, poor network connectivity, and a compressive strength of 0.2 MPa.

[0039] Comparative Example 3 The only difference between this comparative example and Example 1 is that only silicon carbide (1 g) was added, without cryolite, while all other conditions remained the same. The resulting sample showed insufficient lamellar growth, a loose network structure, and a compressive strength of 0.4 MPa.

[0040] The above embodiments demonstrate that by adjusting the raw material ratio and sintering process parameters, the lamellar size and porosity can be controlled within a wide range to obtain ceramic aerogels with different mechanical and thermal insulation properties. The synergistic effect of the cryolite-silicon carbide composite additive is key to the formation of the three-dimensional interlocking network of lamellar crystals; without this additive or by adding only a single component, a high-strength interlocking structure cannot be obtained. Compared with existing technologies, this invention can obtain ceramic aerogels with stable structures and excellent mechanical properties without the need for external binders or freeze-drying.

[0041] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A ceramic aerogel with an α-Al₂O₃ lamellar three-dimensional interlocking network structure, characterized in that, The α-Al2O3 lamellar three-dimensional interlocking network structure ceramic aerogel is formed by α-Al2O3 lamellars overlapping and interlocking to form a three-dimensional continuous network skeleton; the radial dimension of the α-Al2O3 lamellars is 2~15 μm and the thickness is 0.1~0.5 μm.

2. The α-Al₂O₃ lamellar three-dimensional interlocking network structure ceramic aerogel according to claim 1, characterized in that, The porosity of the α-Al2O3 lamellar three-dimensional interlocking network structure ceramic aerogel is 60%~85%.

3. The α-Al₂O₃ lamellar three-dimensional interlocking network structure ceramic aerogel according to claim 1, characterized in that, The α-Al₂O₃ lamellar three-dimensional interlocking network structure ceramic aerogel has a thermal conductivity of ≤0.08 W·m at 25℃. -1 ·K -1 .

4. A method for preparing an α-Al₂O₃ lamellar three-dimensional interlocking network structure ceramic aerogel according to any one of claims 1 to 3, characterized in that, Includes the following steps: (1) Raw material mixing: The organic aluminum precursor and α-Al2O3 powder are mixed at a mass ratio of 1:0.1~1, and a composite sintering aid is added. After ball milling and mixing evenly, a molding slurry is prepared. (2) Molding: The molding slurry is prepared into a blank by gel injection molding process or template foaming method; (3) Drying: The green body prepared in step (2) is dried to obtain the aerogel precursor; (4) Sintering: The aerogel precursor is placed in an air atmosphere and heated to 1100~1300℃ at a heating rate of 1~10℃ / min. It is held for 1~4 hours. The cryolite-silicon carbide synergistic gas phase mass transfer effect drives the in-situ growth of α-Al2O3 lamellar crystals and forms a three-dimensional interlocking network. After sintering, ceramic aerogel is obtained.

5. The preparation method according to claim 4, characterized in that, The organoaluminum precursor in step (1) is selected from aluminum sec-butoxide, aluminum isopropoxide, or aluminum acetylacetone.

6. The preparation method according to claim 4, characterized in that, The particle size of the α-Al2O3 powder in step (1) is 0.1~10 μm.

7. The preparation method according to claim 4, characterized in that, In step (1), the mass ratio of cryolite to silicon carbide in the composite sintering aid is 20 to 1:

1.

8. The preparation method according to claim 4, characterized in that, The amount of composite sintering aid added in step (1) is 1% to 20% of the total mass of the organoaluminum precursor and α-Al2O3 powder.

9. The preparation method according to claim 4, characterized in that, The drying process described in step (3) is atmospheric pressure drying, freeze drying, or supercritical drying.

10. The application of an α-Al2O3 lamellar three-dimensional interlocking network structure ceramic aerogel as described in any one of claims 1 to 3 in aerospace thermal protection and high-temperature insulation.